Developing a Model Proposal to Evaluate the Authenticity of Traditional Housing; Malatya Case Study - Sahin, Murat; Eroğlu, Bahtiyar (My University, 2023)
Anatolia has been used as a settlement area by many civilizations throughout history due to its geopolitical and geographical features. Traditional houses in Anatolia convey the thousands of years of culture and identity of the region where they are located, with their unique architectural style. In this respect, traditional houses appear as the most important cultural heritage values that convey information such as the social, cultural, economic and architectural style of the period. Historical textures have been in change and transformation in the Malatya region, as in every region of Anatolia. However, Malatya has largely lost its traditional houses and texture due to many reasons such as rapid urbanization, unconsciousness, rent, and the destructive effect of time. In this study, which was prepared by addressing this problem, Fuzzy Logic and AHP (Analytical Hierarchy Process) analysis system was used in order to evaluate the authenticity of civil architectural examples located in traditional tissue pieces in the urban area of Malatya and to protect these structures. Thus, it is aimed to develop an authenticity assessment method together with the experts of the subject (conservation experts, architectural historians, art historians). It is aimed to determine the authenticity of the buildings numerically and proportionally with the authenticity evaluation model developed with a systematic setup. Ahmet Kökçü House, located in Yakınca Neighborhood, was chosen as the study area due to reasons such as the fact that it largely preserved its traditional texture as a field study and faced extinction as a result of the rapid urbanization of Malatya's central city wall reaching the border of Yeşilyurt district. With the authenticity assessment model developed in this context, the authenticity of the building was determined by experts and suggestions were made for the preservation of the building.
Keywords: Fuzzy logic; authenticity; Cultural heritage; traditional Malatya houses; analytical hierarchy process (ahp)